2020
DOI: 10.1186/s12964-020-00596-9
|View full text |Cite
|
Sign up to set email alerts
|

YYFZBJS ameliorates colorectal cancer progression in ApcMin/+ mice by remodeling gut microbiota and inhibiting regulatory T-cell generation

Abstract: Background: Progression of Colorectal cancer (CRC) is influenced by single or compounded environmental factors. Accumulating evidence shows that microbiota can influence the outcome of cancer immunotherapy. T cell, one of the main populations of effector immune cells in antitumor immunity, has been considered as a double-edged sword during the progression of CRC. Our previous studies indicate that traditional Chinese herbs (TCM) have potential anticancer effects in improving quality of life and therapeutic eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 59 publications
(52 citation statements)
references
References 69 publications
1
45
0
Order By: Relevance
“…Several recent studies have con rmed the link between dysbiosis of the gut microbiome and colorectal cancer [35,36]. Our previous ndings have con rmed that, ETBF, one of the most regulated monomers by YYFZBJS, promoted the proliferation of tumor cells through immunity [5]. However, no studies investigating the impact of TCM on the balance between gut microbiome and immune cell in the colonic tumorigenesis have been reported.…”
Section: Discussionmentioning
confidence: 85%
See 4 more Smart Citations
“…Several recent studies have con rmed the link between dysbiosis of the gut microbiome and colorectal cancer [35,36]. Our previous ndings have con rmed that, ETBF, one of the most regulated monomers by YYFZBJS, promoted the proliferation of tumor cells through immunity [5]. However, no studies investigating the impact of TCM on the balance between gut microbiome and immune cell in the colonic tumorigenesis have been reported.…”
Section: Discussionmentioning
confidence: 85%
“…However, the development of CRC remains to be completely understood owing to its complexity. Recently, accumulating evidence suggests that the gut microbiota, chronic in ammation, host genetic predisposition, and environmental factors have been linked with the progression of CRC [3,4] We have demonstrated that enterotoxigenic Bacteroides fragilis (ETBF) strains secrete the B. fragilis toxin, severely altered Tregs mediated by YYFZBJS repressed CRC cancer cell growth, along with reduction of the phosphorylation of β-catenin [5].…”
Section: Introductionmentioning
confidence: 94%
See 3 more Smart Citations